2018
DOI: 10.1093/ofid/ofy330
|View full text |Cite
|
Sign up to set email alerts
|

Tropheryma whipplei Endocarditis: Case Presentation and Review of the Literature

Abstract: Whipple’s disease is a rare infective condition, classically presenting with gastrointestinal manifestations. It is increasingly recognized as an important cause of culture-negative endocarditis. We present a case of Whipple’s endocarditis presenting with heart failure. A literature review identified 44 publications documenting 169 patients with Whipple’s endocarditis. The average age was 57.1 years. There is a clear sex predominance, with 85% of cases being male. Presenting symptoms were primarily articular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 50 publications
0
29
0
3
Order By: Relevance
“…Although isolated Whipple's endocarditis without systemic involvement has been reported in the literature [6][7][8], this disease entity is rare. A recent literature review by McGee et al identified 44 publications totaling 169 patients with Whipple's endocarditis [9]. While the incidence of classic Whipple's disease is estimated to be between 1 and 6 new cases per 10,000,000 persons per year worldwide [5], the incidence of isolated Whipple's endocarditis is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although isolated Whipple's endocarditis without systemic involvement has been reported in the literature [6][7][8], this disease entity is rare. A recent literature review by McGee et al identified 44 publications totaling 169 patients with Whipple's endocarditis [9]. While the incidence of classic Whipple's disease is estimated to be between 1 and 6 new cases per 10,000,000 persons per year worldwide [5], the incidence of isolated Whipple's endocarditis is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the prevalence was 26% among sewer workers and 37% among relatives of healthy carriers 2 . A recent literature review by McGee et al 3 reported male predominance (85%) in prevalence rates of TW infection. Interestingly, 52% of patients reported arthralgia (dissimilar to our patient's presentation), and 41% of the patients presented with heart failure, as was observed in our case.…”
Section: Commentmentioning
confidence: 97%
“…Interestingly, 52% of patients reported arthralgia (dissimilar to our patient's presentation), and 41% of the patients presented with heart failure, as was observed in our case. A delay in diagnosis since the appearance of the first nonspecific symptoms was approximately 21 months, and the reported mortality rate was 24% 3 …”
Section: Commentmentioning
confidence: 99%
“…Comorbidities or other predisposing risk factors have been not uniformly reported in the literature [118]. Previous valvular affectation has been documented in 21% of the diagnosed cases, while prosthetic valve replacement previously to the event seems not an important condition (<5% of the available series).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Asthenia and malaise lasting more than six months were notified by the 41.2% of the patients in one series [70]. Other signs such as weight loss or gastrointestinal symptoms have been observed in 25% and 21% of the reported patients [118]. In addition, central nervous system manifestations (i.e., emboli) have been detected in 16% of patients.…”
Section: Clinical Featuresmentioning
confidence: 99%